2011
DOI: 10.1111/j.1525-1594.2010.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine and Hospital Mortality in Critically Ill Patients Undergoing Continuous Renal Replacement Therapy

Abstract: High-dose vasopressor use is associated with increasing mortality in patients with septic shock. We conducted this study to determine if the high-dose of vasopressor used before the initiation of continuous renal replacement therapy (CRRT) is associated with increasing mortality in critically ill patients. We retrospectively reviewed all patients who underwent CRRT in the medical intensive care unit of China Medical University Hospital between 2003 and 2007. The association between mortality and highest vasopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
(35 reference statements)
2
14
0
2
Order By: Relevance
“…Several factors are associated with high mortality during CRRT. The physical condition of patients undergoing CRRT is already poor, and most of them have multiple comorbidities including sepsis and problems with the heart and lungs . The seven significant variables that were selected for the MOSAIC model incorporated hypotension, respiratory failure, unconsciousness, electrolyte and acid–base imbalance, liver dysfunction, and adverse immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors are associated with high mortality during CRRT. The physical condition of patients undergoing CRRT is already poor, and most of them have multiple comorbidities including sepsis and problems with the heart and lungs . The seven significant variables that were selected for the MOSAIC model incorporated hypotension, respiratory failure, unconsciousness, electrolyte and acid–base imbalance, liver dysfunction, and adverse immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The physical condition of patients undergoing CRRT is already poor, and most of them have multiple comorbidities including sepsis and problems with the heart and lungs. [23][24][25][26] The seven significant variables that were selected for the MOSAIC model incorporated hypotension, respiratory failure, unconsciousness, electrolyte and acidbase imbalance, liver dysfunction, and adverse immune response. However, serum creatinine was not a relevant factor in high mortality, which suggests that the original prediction models needed modification.…”
Section: Discussionmentioning
confidence: 99%
“…If the target MAP could not be achieved, the large dose of vasoactive drug would result in resuscitation failure and severe adverse effects. A clinical study showed dopamine in dose of ≥20 μg/kg/min and NE in dose of ≥0.3 μg/kg/min were significantly linked to increased mortality in critically ill patients . ECMO can provide respiratory and circulatory support to DBD donor, thus avoiding liver and kidney function damage caused by vasoactive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that high-dose vasopressor is associated with increased mortality. Study from Wang et al [30] found that norepinephrine doses equal or above 0.3 μg/kg/min were independently linked to mortality, HR 1.77 (95% IC 1.23 to 2.52, P = 0.001). Critically ill patients treated with high doses of norepinephrine before the initiation of CRRT have a very high mortality rate regardless of the stage of the AKI [30].…”
Section: Discussionmentioning
confidence: 94%